There exists a monic 10th-degree polynomial f ( x ) whose graph intersects the graph of g ( x ) = x 9 − 3 x 8 + 1 7 x at all x ∈ { 1 , 2 , 3 , ⋯ , 1 0 } .
If the roots of f ( x ) are r 1 , r 2 , r 3 , … , r 1 0 , find i = 1 ∑ 1 0 r i 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We note that
f ( x ) − g ( x ) f ( x ) − x 9 + 3 x 8 − 1 7 x ⟹ f ( x ) = ( x − 1 ) ( x − 2 ) ( x − 3 ) ⋯ ( x − 1 0 ) = x 1 0 − 5 5 x 9 + 1 3 2 0 x 8 − ⋯ + k = 1 ∏ 1 0 k = x 1 0 − 5 4 x 9 + 1 3 1 7 x 8 − ⋯ + k = 1 ∏ 1 0 k
By Vieta's formula , i = 1 ∑ 1 0 r i = 5 4 and i = j ∑ 1 0 r i r j = 1 3 1 7 and by Newton's sums or identities ,
i = 1 ∑ 1 0 r i 2 = ( i = 1 ∑ 1 0 r i ) 2 − 2 i = j ∑ 1 0 r i r j = 5 4 2 − 2 × 1 3 1 7 = 2 8 2
Problem Loading...
Note Loading...
Set Loading...
Since f ( x ) is monic and equal to x 9 − 3 x 8 + 1 7 x for x ∈ { 1 , 2 , . . . , 9 , 1 0 } , we know:
f ( x ) − x 9 + 3 x 8 − 1 7 x = ( x − 1 ) ( x − 2 ) . . . ( x − 1 0 )
We can see then that both sides of the equation are a 10th-degree polynomial, therefore:
f ( x ) = ( x − 1 ) ( x − 2 ) . . . ( x − 1 0 ) + x 9 − 3 x 8 + 1 7 x
Since we now know f ( x ) , we can use vieta to find the sum of its squared roots:
r 1 2 + r 2 2 + . . . + r 1 0 2 = ( r 1 + r 2 + . . . + r 1 0 ) 2 − 2 ( r 1 r 2 + r 1 r 3 + . . . + r 9 r 1 0 )
We can see in order to find the sum of the squared roots, we need to know the coefficient of the x 9 term and the x 8 term.
x 9 term of ( x − 1 ) ( x − 2 ) . . . ( x − 1 0 ) :
i = 1 ∑ 1 0 − i = − 5 5
Adding the lone x 9 :
− 5 5 x 9 + x 9 = − 5 4 x 9
x 8 term of ( x − 1 ) ( x − 2 ) . . . ( x − 1 0 ) :
1 ( 2 + 3 + . . . + 1 0 )
+ 2 ( 3 + 4 + . . . + 1 0 )
+ 3 ( 4 + 5 + . . . + 1 0 )
⋮
+ 9 ( 1 0 )
= i = 1 ∑ 1 0 i ( 5 5 − 2 i 2 + i )
= i = 1 ∑ 1 0 5 5 i − 2 1 i 2 − 2 1 i 3
= 2 ( 5 5 ) ( 1 0 ) ( 1 1 ) − 1 2 ( 1 0 ) ( 1 1 ) ( 2 1 ) − 8 ( 1 0 ) 2 ( 1 1 ) 2
= 3 0 2 5 − 1 9 2 . 5 − 1 5 1 2 . 5
= 1 3 2 0
Adding the − 3 x 8 :
1 3 2 0 x 8 − 3 x 8 = 1 3 1 7 x 8
Therefore,
i = 1 ∑ 1 0 r i 2 = ( − 5 4 ) 2 − 2 ⋅ 1 3 1 7 = 2 8 2